Essential Oil and Fatty Acid Composition of Endemic Gypsophila laricina Schreb. from Turkey - Servi, Huseyin; Keskin, Betul Eren; Celik, Sezgin; Budak, Umit; Kababiyik, Bilva (TURKISH PHARMACISTS ASSOC, 2019)
Objectives: Gypsophila species have very high medicinal and commercial importance and contain interesting natural substances. However, there is no report on the essential oil or fatty acid composition of any Gypsophila species. This prompted us to investigate the essential oil and fatty acid composition of Gypsophila laricina Schreb. Materials and Methods: Plant materials were collected during the flowering period. The essential oil composition of the aerial parts of G. laricina Schreb. was analyzed by gas chromatography and gas chromatography-mass spectrometry. The fatty acid compositions were analyzed by gas chromatography-mass spectrometry. Results: Sixty-six and ten compounds were identified in the essential oil and fatty acid of G. laricina Schreb., respectively. The major components of the essential oil were hexadecanoic acid (27.03%) and hentriacontane (12.63%). The main compounds of the fatty acid were (Z, Z)-9,12-octadecadienoic acid methyl ester (18: 2) 40.4%, (Z)-9-octadecenoic acid methyl ester (18: 1) 35.0%, and hexadecanoic acid methyl ester (16:0) 13.0%. Conclusion: The results showed that the fatty acid composition is rich in polyunsaturated fatty acids. The essential oils of G. laricina Schreb. were dominated by fatty acid derivatives and n-alkanes. We think the results obtained from this research will stimulate further research on the chemistry of Gypsophila species.
Keywords: Gypsophila laricina; essential oil; fatty acid; CHEMICAL-COMPOSITION; ANTIMICROBIAL ACTIVITY; BIOLOGICAL-ACTIVITIES; VOLATILE COMPOUNDS; L.; CONSTITUENTS; CHEMOTYPES; COMPONENTS; Pharmacology & Pharmacy